Relationship of difficult endoscopic retrograde cholangiopancreatography cannulation and visual characteristics of papilla - Amjad Khan; Syeda Qumreen Ahmad; Tayyab Saeed Akhtar; Hamama Tul Bushra; Muhammad Imran; Javeria Zahid Khan; Sanjida Shah; Nadia Haddayat; Saima Mushtaq; Yalin Dong; Weiyi Feng; Yu Fang (JGH Open)
Abstract Background and Aim Endoscopic retrograde cholangiopancreatography (ERCP) is commonly used to diagnose and treat bile duct and pancreatic disorders. Successful cannulation of the papilla is crucial for the effectiveness of ERCP; however, sometimes, it can be challenging to achieve. This study explores the relationship between net difficult ERCP cannulation with bile visibility, papilla orifice visibility, and papilla position and compares it with successful cannulation. Methods These data were collected from the ERCP database at the Center for Liver Disease, Holy Family Hospital, Rawalpindi, between November 2019 and November 2022. IBM SPSS version 26.0 software was used for statistical analysis. Results The study included 329 patients, with 186 (56.6%) female and 143 (43.5%) male participants. Most patients were in the 39–48 age group (28.3%), with a mean age of 51 ± 1. Bile visibility was noted in 268 (81.5%) cases, papilla orifice visibility in 296 (90%) participants, atypical papilla in 20 (6.1%), and typical papilla in 309 (93.9%) participants. Bile visibility (P = 0.004) and papilla orifice visibility (P = 0.006) were significantly associated with successful cannulation, while papilla position (P = 0.116) was not. Significant associations were also found between difficult cannulation and bile visibility (P = 0.000), papilla orifice visibility (P = 0.000), and papilla position (P = 0.000). Conclusion Understanding this relationship can improve success rates and reduce complications associated with difficult cannulation during ERCP procedures. Further research is needed to establish clear correlations and guidelines for endoscopists to plan appropriate strategies for challenging cases.